2018
DOI: 10.1016/j.jclepro.2017.09.144
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the scaling-up of community energy niches through strategic niche management theory: Insights from Finland

Abstract: a b s t r a c tThe growing phenomenon of civil society involvement in renewable energy generation has attracted researchers' interest. However, rather little is known of how a diverse and relatively small sector such as community energy could scale up and promote a change in energy production. We examine this issue through the lens of Strategic Niche Management (SNM) and conceptualize community energy as a sociotechnical niche that holds the potential to promote a transition to renewable energy. Drawing on int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Theory suggests that successful niches can influence the regime by enabling replication of projects within the niche, bringing about changes through multiple small initiatives; by enabling constituent projects to grow in scale and attract more participants; and by facilitating the translation of niche ideas into mainstream settings [15]. In the process of developing niches and making them more robust, intermediaries appear to be of particular significance [19,21,24,95,96]. Therefore, SNM mainly addresses issues related to alleviating barriers and opening up regimes for the acceptance and breakthrough of LLCEIs.…”
Section: Strategies Intermediaries Usementioning
confidence: 99%
“…Theory suggests that successful niches can influence the regime by enabling replication of projects within the niche, bringing about changes through multiple small initiatives; by enabling constituent projects to grow in scale and attract more participants; and by facilitating the translation of niche ideas into mainstream settings [15]. In the process of developing niches and making them more robust, intermediaries appear to be of particular significance [19,21,24,95,96]. Therefore, SNM mainly addresses issues related to alleviating barriers and opening up regimes for the acceptance and breakthrough of LLCEIs.…”
Section: Strategies Intermediaries Usementioning
confidence: 99%
“…Reviewing a decade of Strategic Niche Management (SNM) research, Schot and Geels [5] indicate that the attention to niche-internal dynamics has gone at the expense of understanding their external dynamics and today this still applies [9,17]. Like SNM, studies of Transition Management (TM) have argued that experimentation is key to stimulate upscaling [13].…”
Section: Conceptualizing Constraints On Upscalingmentioning
confidence: 99%
“…Strategic niche management research has long demonstrated that sustainable innovation journeys are facilitated through experimentation in protected spaces that allow co-evolution of user practice, technology and regulatory structures (Ruggiero et al 2018;Schot and Geels 2008). This is required to prevent early rejection (Raven 2007).…”
Section: Urban Sustainability Experiments and Transitionmentioning
confidence: 99%